THE EFFECT OF DRINK BANANA JUICE ON THE LEVEL OF ANXIETY PLAYERS HANDBALL WOMEN PRA KEJURNAS - Sari, Nuril Sekar (Jurnal Kesehatan Olahraga, 2019)
In sport achievement, anxiety always comes before and while competing. Ambon banana contains an active vitamin C, B complex, B6, and serotonin that play a role to reduce anxiety level and as neurotransmitter in expediting brain function. This study aims to know the influence of giving banana juice on the anxiety level among female handball players in pre national championship. This study is an experimental study with pre-post test design. The sample was taken by using simple random sampling. 14 players (7 players as the experimental group and 7 players as the controlled group). Data analysis was descriptive analysis, normality test data, and t-test. The result shows that experimental group have P value is 0.000 < 0.05 and 0.030 < 0.05 for the controlled group. This shows that there is a significant difference between the experimental group and the controlled group on the anxiety level among female handball players in pre national championship. Therefore, consuming banana juice in two hours before the competition could be one of the solutions to decrease the anxiety level of female handball players in pre national championship. Keywords: handball, anxiety, banana juice